2020
DOI: 10.1007/978-3-030-48721-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Model Order Reduction for Fluid Flow

Abstract: In the past decade, model order reduction (MOR) has been successful in reducing the computational complexity of elliptic and parabolic systems of partial differential equations (PDEs). However, MOR of hyperbolic equations remains a challenge. Symmetries and conservation laws, which are a distinctive feature of such systems, are often destroyed by conventional MOR techniques which result in a perturbed, and often unstable reduced system. The importance of conservation of energy is well-known for a correct numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The preservation of secondary conservation is also of importance in numerical schemes [40] and its importance in ROM stability has been emphasized by Afkham et al [41]. Both the FOM and ROM solutions are based on the primary conservation laws, but secondary conservation (kinetic energy, k, and entropy, s) is evaluated by means of the following, Kinetic Energy:…”
Section: Conservation Law Preservationmentioning
confidence: 99%
“…The preservation of secondary conservation is also of importance in numerical schemes [40] and its importance in ROM stability has been emphasized by Afkham et al [41]. Both the FOM and ROM solutions are based on the primary conservation laws, but secondary conservation (kinetic energy, k, and entropy, s) is evaluated by means of the following, Kinetic Energy:…”
Section: Conservation Law Preservationmentioning
confidence: 99%
“…Ahmed et al 48 present a comprehensive review of the state of the art in closure modeling for projection-based ROMs. It has been shown that maintaining the conservation properties of the governing equations is critical in ROM development 49 . A method demonstrated by 50 generates stable non-linear ROMs by minimizing the least-squares residual of the projected solution, yielding in a symmetrized and linearly stable ROM.…”
Section: Projection-based Reduced-order Modelingmentioning
confidence: 99%
“…We begin by applying sparse sampling and interpolation to the non-linear equation residual r in Eq. 34 qn…”
Section: Hyper-reductionmentioning
confidence: 99%
“…While these methods can enable stable ROMs, they can compromise the conservative properties of the governing equations during the model reduction procedure. Afkham et al [34] highlighted the importance of preserving the conservative form of the governing equations in ROM development.…”
Section: Introductionmentioning
confidence: 99%